Numerical simulation of aquifer thermal energy storage using surface-based geologic modelling and dynamic mesh optimisation - Regnier,G; Salinas,P; Jacquemyn,C; Jackson,MD (Hydrogeology Journal, 2022)
Aquifer thermal energy storage (ATES) has significant potential to provide largescale seasonal cooling and heating in the built environment, offering a low-carbon alternative to fossil fuels. To deliver safe and sustainable ATES deployments, accurate numerical modelling tools must be used to predict flow and heat transport in the targeted aquifers. This paper presents a simulation methodology for ATES based on surface-based geologic modelling (SBGM) and dynamic mesh optimisation (DMO). DMO has been previously applied in other fields of computational fluid dynamics to reduce the cost of numerical simulations. DMO allows the resolution of the mesh to vary during a simulation to satisfy a user-defined solution precision for selected fields, refining where the solution fields are complex and coarsening elsewhere. SBGM allows accurate representation of complex geological heterogeneity and efficient application of DMO. The paper reports the first systematic convergence study for ATES simulations, and demonstrates the application of these methods in two ATES scenarios: a homogeneous aquifer, and a realistic heterogeneous fluvial aquifer containing meandering, channelised sand bodies separated by mudstones. It is demonstrated that DMO reduces the required number of mesh elements by a factor of up to 22 and simulation time by a factor of up to 15, whilst maintaining the same accuracy as an equivalent fixed mesh. DMO offers significant potential to reduce the computational cost of ATES simulations in both homogeneous and heterogeneous aquifers.